Antimicrobial Use and Resistance in Plant Agriculture: A One Health Perspective - Sally A. Miller; Jorge Pinto Ferreira; Jeffrey T. LeJeune (Agriculture, 2022)
Bactericides, fungicides, and other pesticides play an important role in the management of plant diseases. However, their use can result in residues on plants and in the environment, with potentially detrimental consequences. The use of streptomycin, oxytetracycline, copper-based products, and some fungicides is correlated with increased resistance among plant pathogens to these agents. Likewise, the recent rise in the incidence of environmental triazole fungicide-resistant Aspergillus fumigatus, the cause of aspergillosis in humans, has caused concern, particularly in Europe. Through horizontal gene transfer, genes can be exchanged among a variety of bacteria in the plant production environment, including phytopathogens, soil bacteria, and zoonotic bacteria that are occasionally present in that environment and in the food chain. Through mechanisms of horizontal gene transfer, co-resistance, cross-resistance, and gene up-regulation, resistance to one compound may confer resistance and multi-drug resistance to other similar, or even very dissimilar, compounds. Given the global rise in antimicrobial-resistant (AMR) organisms, and their effects on plant, animal, and human health, the prudent use of pesticides is required to maintain their effectiveness for food security and sustainable production, and to minimize the emergence and transmission of AMR organisms from horticultural sources.